Research on the Disintegration Characteristics of Carbonaceous Mudstone and Properties of Modified Materials. (9th December 2019) - Liu, Xinxi; Li, Yu; Li, Shengnan; Zhou, Yanming
Abstract : This work presents the results of an experimental investigation aimed to study the disintegration of carbonaceous mudstone and properties of modified materials. The mineralogical composition of carbonaceous mudstone was determined with X-ray diffraction. The microscopic characteristics of carbonaceous mudstone disintegration were determined with scanning electron microscopy. The surface modification effect of carbonaceous mudstone was researched by comparative tests on coatings' hydrophobic property, fastness, and waterproof before and after modification, and the modification mechanism of polymer-cement composite modified carbonaceous mudstone was analyzed. The results show that the mineral composition of carbonaceous mudstone mainly contains illite, quartz, and kaolinite. It is found that the disintegration of carbonaceous mudstone can be divided into external factors and internal factors. External factors are water and temperature difference, and internal factors are the swelling of the kaolinite and illite mineral particles. There are differences in the modification effects under different cement dosage. When the cement dosage is 30%, the modification effect is the best. The results may provide a reference for the prevention and control of soft rock slopes.